Cara Menyikat Gigi Yang Baik Dan Benar Sebagai Kontrol Plak Gigi Untuk Mencegah Penyakit Karies Gigi Dan Kuratif Sederhana Pada Siswa Smpn 2 Martapura Propinsi Kalimantan Selatan - Kisworo Utami, Naning; Amperawati, Metty; Nurwati, Bunga; Miha, Aninun; Askya, Rachima; Ali Akbar, Muhammad (UPPM Poltekkes Kemenkes Banjarmasin, 2023)
Dental and oral health problems are still something that needs attention, it can be seen that 90% of the Indonesian population suffers from dental and oral diseases, including dental caries and periodontal disease. In the city of Banjarbaru, only 4.04% of the population goes to medical personnel, the daily brushing behavior is 97.88% and the correct time for brushing teeth is only 2.06%. Currently, the highest prevalence of dental and oral diseases is dental caries and periodontal disease which are caused by dental plaque. The aim of community service is: a) How to brush your teeth properly and correctly b). Carry out a dental plaque examination, c). Mass tooth brushing and d). Simple Curative for students at SMPN 2 Martapura, South Kalimantan Province. The number of community service respondents was 100 students, located at SMPN 2 Martapura, South Kalimantan Province. On the day of the activity, 96 students of SMPN 2 Martapura were present, beforehand they were given a questionnaire, after that there was counseling on how to brush teeth properly and correctly, the right time to brush teeth, examination of DMF-T and plaque to see OHIS, simple curative by means of fillings with ART and re-examined. The results of the activity obtained were as follows: 60% of students filled in the questionnaire correctly, the average DMF-T score = 4.3 and the average OHI-S score = 1.59. The conclusion is that based on the results of the DMF-T and OHI-S examinations, the results were in the moderate category. It is recommended to carry out treatment which includes: cleaning tartar, fillings and extractions at a health center, hospital or independent dental clinic.